Optimization of One-Time Fertilization Scheme Achieved the Balance of Yield, Quality and Economic Benefits of Direct-Seeded Rice - Shuang Cheng; Zhipeng Xing; Chao Tian; Wen’an Weng; Qun Hu; Hongcheng Zhang (Plants, 2023)
There is limited information available to assess the impact of one-time fertilization on the yield, quality, and economic benefits of direct-seeded rice. This study reports the effects of three one-time fertilizer treatments (BBU1, BBU2, and BBU3) on the yield, quality, and economic benefits of direct-seeded rice, where controlled-release nitrogen (N) fertilizer (CRNF) provided 50%, 60%, and 70% of the total N (270 kg N ha−1), and the control treatment (CK) was a split application of conventional urea (CU). The results showed that the yield of direct-seeded rice decreased significantly (p < 0.05) with the increased application ratio of CRNF under one-time fertilization, which was mainly related to N accumulation between the heading time and maturity stages. Compared to CK, the one-time fertilization treatments (BBU1, BBU2, and BBU3) maintained high milling quality, with significantly reduced chalkiness (p < 0.05), which could be related to the slow rate of N release from the CRNF. In addition, the one-time fertilization treatments reduced the protein content and increased the amylose content of the milled rice, which significantly improved the eating quality (p < 0.05). Furthermore, there was no significant difference in yield and economic benefit between BBUI and CK (p > 0.05). Overall, CRNF replacing conventional urea with 50% total N could be helpful to reduce fertilization frequency, achieve high yield and high economic efficiency, and improve rice quality of direct-seeded rice under one-time fertilization.